Postmastectomy-Postirradiation Atypical Vascular Lesion of the Skin: Report of 2 Cases - P. S. Jayalakshmy; Aswathy P. Sivaram; Joy Augustine; P. Bindu (Hindawi Limited, 2012)
The spectrum of vascular lesions developing in breast or chest wall skin following lumpectomy or mastectomy and radiation is wide and ranges from atypical vascular lesions with a benign clinical behaviour to frankly malignant, angiosarcoma ranging histologically from well to poorly differentiated variety. Postmastectomy-postirradiation atypical vascular lesions (AVLs) are rare and develop in the skin adjacent to the mastectomy scar. About hundred cases have been reported in the literature so far. AVLs have also been reported in patients after breast conservation surgery within the breast parenchyma or in the skin around the scar. The incidence appears to be rising. The exact reason for this is not known. The newer modalities of radiation therapy may be contributory to the pathogenesis. More studies have to be done in this area to prove the causal relationship. We are reporting the cases of 2 patients with carcinoma of breast who developed postmastectomy-postirradiation atypical vascular lesions. The cases were received in our department within a 6-month period.